Bekleyen Sipariş Durumunda Sürekli Gözden Geçirmeye Dayalı Olasılıklı (r,q) Stok Kontrol Modeli Ve Depo Yapısı - Yılmaz, Ömer Faruk (Fen Bilimleri Enstitüsü, 2013)
Günümüzde müşteriler, hızlı ve güvenilir hizmet talep etmektedirler. Bu doğrultuda müşterilerin taleplerini karşılamak için işletmelerin stok kontrolüne ve depo yönetiminine önem vermesi gerekmektedir. Stok kontrol fonksiyonunun etkin bir şekilde gerçekleştirilmesi için deterministik yerine olasılıklı talep yapılarının göz önünde bulundurulması önem arz etmektedir. Depo ve stok değişkenlerini bir arada bulunduran ve doğru değişkenlerle gerçekleştirilecek modeller işletmelere büyük fayda sağlayacaktır. Kurulacak olan modellerde stok yetersizliği, ürün yıpranmaları v.b durumlara yer verilirse gerçekçi bir yaklaşım elde edilecektir. Bu çalışmada da hem müşteri ihtiyaçlarına cevap verebilmek için hem de gerçek durumları modellemek adına maliyet olarak etkin olan değişkenler kullanılmıştır. Çevrim hizmet düzeyi değiştirilerek maliyetler ve sipariş karşılanma oranı üzerinde ki etkisi incelenmiştir. Stok yıpranmaları ve stok yetersizliği durumları ele alınarak farklı çevrim hizmet düzeyleri için edinilmesi gereken ek kapasite miktarları belirlenmeye çalışılmıştır. Model toplam dönemsel maliyetin en küçüklenmesi amacıyla çözülmüş ve stok kararları doğru olarak belirlenmeye çalışılmıştır. Yayın araştırması sonucunda sipariş toplama aktivitesinin önemini vurgulayan çalışmaların çok sayıda olduğu, yıpranmaları ele alan çalışmaların yeterince olduğu ve elde bulundurmama durumunun varyasyonlarıyla gerçekleştirilen çok sayıda çalışma olduğu görülmüştür. Bu çalışmada olduğu gibi stok değişkenlerini ayrı depo değişkenlerini ayrı olarak ele alan çalışmaların yanı sıra bu değişkenleri ortak olarak modelleyen çalışmaların sayısıda oldukça fazladır. Bu modellerin çözümünde sezgisel yöntemlerin kullanımı ağır basmaktadır. Bu tez çalışması kapsamında depo ve stok değişkenleri birleştirilmiş ve toplam maliyeti en küçükleyerek stok kararlarını verebilmek amacıyla model çözülmüştür. Çözüm için sezgisel bir yöntem uygulanmış ve farklı çevrim hizmet düzeyleri için yöntemin etkinliği sınanmıştır. Uygulanan sezgisel yöntemde model iki alt modele ayrılmış ve ilk olarak stok alt modelinin çözümü sağlanmıştır. Stok alt modelinin sonuçları sabit tutularak depo alt modeli çözülmüştür. Tez çalışması toplam altı bölümden oluşmaktadır. Tez çalışmasının ilk bölümünde çalışmada ele alınan durumlar genel olarak açıklanmıştır. İkinci bölümde, stok tanımları, stok ana ve alt maliyet kalemleri, deterministik ve stokastik stok kontrol modelleri ayrıntılı olarak incelenmiştir. Üçüncü bölümde, çalışmada ele alınan tüm değişkenlerle ilgili olarak daha önce literatürde gerçekleştirilmiş çalışmalar ayrıntılı olarak incelenmiştir. Bu çalışmalardan çıkarılan sonuçlar aktarılmıştır. Dördüncü bölümde, çözülecek olan stok kontrol modeli oluşturularak bu problemin tanımı, notasyonları, değişkenleri detaylı olarak incelenmiştir. Beşinci bölümde, uygulama gerçekleştirilmiş ve modelin gerçek bir sistemle olan uyumu analizlerle değerlendirilmiştir. Altıncı ve son bölümde, tüm tez çalışmasının genel bir değerlendirmesi yapılarak, ilerleyen dönemde gerçekleştirilebilecek yeni çalışmalar sunulmuştur.

Nowadays, managers are faced with the need to deliver a high service level with minimal warehouse and inventory cost. As it has been shown in surveys, the order picking activity represents 65% of the total cost and 50% of the workforce of a warehouse. In the case of distribution warehouses, this proportion is even more important because the main activity (the only added value) is to receive pallets of items from vendors, stock them and deliver customer orders containing different items. In addition, with the improvement in information technology, it becomes possible to develop tools which can help managers to handle warehouse and inventory issues more efficiently. At all classical levels of decision (strategic, tactical and operational), warehouse managers have to tackle problems which can be divided into two broad classes: warehouse management and inventory management problems. Regarding warehouse management issues, managers have to decide where to assign the products inside the warehouse. Concerning inventory management, managers must decide which product, and how much of each product need to be stored in the warehouse. The forward–reserve problem (FRP) is the problem of assigning products to the forward and reserve areas in order to reduce the overall work content in order picking. Nowadays, most warehouses are divided into two areas: forward and reserve. The forward area is used for broken-case and full-case picking and the reserve area is used for pallet picking and reserve storage. Once a product is stored in the forward area (respectively, the reserve area), all picks must be performed from the forward area (respectively, the reserve area). When the inventory of an item stored in the forward area reaches its reorder point an internal replenishment is performed (from the reserve area to the forward area). The forward area is usually a smaller area than the reserve area where order picking takes less time and is then less costly. The critical decision concerns the choice of the products which will be stored in the forward area. Indeed, if all products are located in the forward area, the size of this area increases and the advantage of lower order picking cost vanishes. The aim of inventory management is to minimize total operating costs while satisfying customer service requirements. In order to accomplish this objective, an optimal ordering policy must be determined by answering to questions such as when to order and how much to order. The operating costs taken into account are the procurement costs, the holding costs and the shortage costs which are incurred when the demand of a client cannot be satisfied (either lost sales costs or backorder costs). There exist different inventory policies: periodic review policy and the continuous review policy. The first policy implies that the stock level will be checked after a fixed period of time and an ordering decision will be made in order to complete the stock to an upper limit (order up to point), if necessary. In the second policy, the stock level will be monitored continuously. A fixed quantity will be ordered when the stock level reaches a reorder point. The order quantity will only be delivered after a fixed lead time and shortage can exist if the inventory is exhausted before the receipt of the order quantity. Those basic policies can be adapted to take into account special situation such as single or multi-item models, single or multi-period models, deterministic or stochastic demands, and lost sales or backorder. Dissertation consider a warehouse composed of a reserve area and a forward area. Concerning the warehouse costs, dissertation have taken into account the cost of advance replenishment of the forward area and the cost of concurrent replenishment of the forward area. The cost of advance replenishments of product i occurs once per picking period if product i is assigned to the forward area The cost of concurrent replenishment depends on the number of concurrent replenishments which occur during the picking period. The warehouse cost contains also picking cost in the forward area (respectively, the reserve area) which depends on the expected number of picks during the picking period. Order picking is generally recognized as the most expensive warehouse operation, because it tends to be either very labor intensive or very capital intensive. Managing the order picking process requires the organization of the orders to be picked and the material handling operations of the picking. In this dissertation, decompose global model in an inventory sub model and a warehouse submodel. Those two submodels are solved sequentially: first the inventory submodel is solved and then the optimal value of the inventory variables are fixed and used to solve the warehouse submodel. The inventory submodel is obtained by eliminating from global model costs and constraints related to the warehouse problem. I obtain a nonlinear inventory model with storage and inventory constraints. In this submodel, warehouse variables still appear in order to model the ordering cost and the capacity constraints. To render this inventory submodel independent of warehouse decisions, the ordering costs are approximate and the two capacity constraints are relaxed into one global capacity constraint. I obtain a linear mixed integer multi-item inventory control model with one capacity constraint. In order to solve this inventory submodel, dualize the inventory and storage constraints and solve the lagrangian of this multi-product inventory submodel. The optimal value of the inventory variables is then used to solve the warehouse submodel. This warehouse submodel is obtained by eliminating costs and constraints related to the inventory problem in the global model and by fixing the value of the inventory variables to the value obtained when solving the inventory submodel. We obtain a mixed integer model where the two capacity constraints (one for each warehouse area) are considered in order to obtain a feasible solution. The organization of the dissertation is as follows. Chapters 1 give general topics. Chapters 2 give comprehensive inventory definitions, cost of inventories, deterministic and sthochastic inventory control models. Chapters 3 give a comprehensive literature survey on warehouse operation and inventory management. The scope of this survey is not limited to the specific problem I studied, but covers most of the important topics in the warehouse and inventory literature. Chapters 4 give decompose global model in an inventory sub model and a warehouse submodel. Those two submodels are solved sequentially in chapter 5: first the inventory submodel is solved and then the optimal value of the inventory variables are fixed and used to solve the warehouse submodel. Finally, research results are summarized and future directions are given in chapter 6.
(r,q) Continuous Review Inventory Policy With Backorder For Warehouse
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2012
Keywords: Stok Kontrol Politikaları; Birincil ikincil alan problemi; servis düzeyi; Inventory control policy; Forward reserve problem; service level.